Electronic circuit design for RF energy harvesting using 28 nm FD‐SOI technology. Issue 6 (24th April 2018) - Awad, M.; Benech, P.; Duchamp, J. M.
Abstract: In this article, a voltage doubler circuit designed using 28 nm FD‐SOI technology has been studied for electromagnetic energy harvesting. NLVT transistor type is chosen and used as a diode for the realization of a Dickson voltage doubler circuit. Moreover, the impact of back gate polarization on circuit performance has been analyzed. The optimization of the circuit along with the measurement results has been presented (1.19 V for 1 stage at −26.3 dBm @ 2.45 GHz).